Terraced landscapes in Slovenia - Ažman Momirski, Lucija; Kladnik, Drago (Acta geographica Slovenica, 2009)
Slovenia is a country of exceptionally diverse landscapes at the intersection of four major European macroregions: the Alpine, Pannonian, Dinaric, and Mediterranean regions. Terraces, which are a characteristic Mediterranean landscape element, occur in all landscape types, but they vary in terms of density, purpose, and current function. Terraces, which define the most characteristic terraced landscape, are most common in the Mediterranean environment. However, they are also common in Karst-Dinaric landscapes and the wine-growing Pannonian hills, but are more unusual in mountainous Alpine regions, where they occur especially in transition areas to Mediterranean landscapes. Different types of terraces are defined by their purposes: agricultural, viticultural, and fruit-growing. The first type is found across Slovenia, whereas the second and third types are found in hills with favorable climates for cultivating grapes and fruit trees. Agricultural terraces are older; with the declining role of agriculture, increased social mobility, and an ageing and insufficient agricultural workforce, these terraces have lost their former role and their former fields are now almost entirely replaced by meadows. With the exception of the Mediterranean region and some of the Dinaric regions, wine-growing terraces and the less common fruit-growing terraces are the product of modern, mechanized farming, and a different understanding of the quality of vineyard production. This requires greater separation between rows to allow the use of farm machinery between grapevines set further apart.